Conjugative plasmids inhibit extracellular electron transfer in Geobacter sulfurreducens - Fessler, Mathias; Madsen, Jonas Stenløkke; Zhang, Yifeng (Frontiers in Microbiology, 2023)
Geobacter sulfurreducens is part of a specialized group of microbes with the unique ability to exchange electrons with insoluble materials, such as iron oxides and electrodes. Therefore, G. sulfurreducens plays an essential role in the biogeochemical iron cycle and microbial electrochemical systems. In G. sulfurreducens this ability is dependent on electrically conductive nanowires that link internal electron flow from metabolism to solid electron acceptors in the extracellular environment. Here we show that when carrying conjugative plasmids, which are self-transmissible plasmids that are ubiquitous in environmental bacteria, G. sulfurreducens reduces insoluble iron oxides at much slower rates. This was the case for all three conjugative plasmids tested (pKJK5, RP4 and pB10). Growth with electron acceptors that do not require expression of nanowires was, on the other hand, unaffected. Furthermore, iron oxide reduction was also inhibited in Geobacter chapellei, but not in Shewanella oneidensis where electron export is nanowire independent. As determined by transcriptomics, presence of pKJK5 reduces transcription of several genes that have been shown to be implicated in extracellular electron transfer in G. sulfurreducens, including pilA and omcE. These results suggest that conjugative plasmids can in fact be very disadvantageous for the bacterial host by imposing specific phenotypic changes, and that these plasmids may contribute to shaping the microbial composition in electrode-respiring biofilms in microbial electrochemical reactors.